Student Study Motivation Viewed From Intrinsic Orientation Objectives in Learning Mathematical Statistics - Nurfalah, Edy; Rahayu, Puji (Prosiding SNasPPM, 2023)
This research aims to describe the study motivation in terms of indicators of students' intrinsic orientation goals in learning mathematical statistics. The research methodology used is descriptive quantitative about study motivation in terms of indicators of intrinsic orientation objectives after conducting microsite-based media development research using the research and development method and implemented in learning in mathematical statistics courses. By using microsite-based educational media, student study motivation in terms of indicators of student intrinsic orientation goals is included in the strong category with an average percent score reaching 80% with an increase reaching 11%.